Isolation of Atlantic halibut pituitary hormones by continuous-elution electrophoresis followed by fingerprint identification, and assessment of growth hormone content during larval development - Einarsdóttir, Ingibjörg E. (2014)
Continuous-elution electrophoresis (CEE) has been applied to separate putative hormones from adult Atlantic halibut pituitaries. Soluble proteins were separated by size and charge on Model 491 Prep Cell (Bio-Rad), where the homogenate runs through a cylindrical gel, and protein fractions are collected as they elute from the matrix. Protein fractions were assessed by SDS–PAGE and found to contain purified proteins of molecular size from 10 to 33 kDa. Fractions containing proteins with molecular weights of approximately 21, 24, 28 and 32 kDa, were identified as putative growth hormone (GH), prolactin, somatolactin and gonadotropins, respectively. These were analyzed further by mass spectrometry and identified with peptide mass protein fingerprinting. The CEE technique was used successfully for purification of halibut GH with a 5% yield, and appears generally well suited to purify species-specific proteins often needed for research in comparative endocrinology, including immunoassay work. Thus, the GH obtained was subsequently used as standards and iodination label in a homologous radioimmunoassay, applied to analyze GH content through larval development in normally and abnormally metamorphosing larvae. As GH is mainly found in the pituitary, GH contents were analyzed in tissue extracts from the heads only. The pituitary GH content increases proportionally to increased larval weight from first feeding to metamorphic climax. No difference in relative GH content was found between normal and abnormal larvae and it still remains to be established if GH has a direct role in metamorphosis.